Teaching Descartes’ First Meditation With Digital Humanities: A Farewell From the Didactics of Philosophy - Kotnik, Rudi (Od filozofije poučevanja do poučevanja filozofije: Festschrift Rudi Kotnik, 2025)
Although the paper can be read as a commentary on digital presentation or as a text introducing digital presentation, the reader requires both approaches. They present an approach to teaching Descartes’ First Meditation in a way that complements the usual linear reading with the opportunity to comprehend each paragraph in the structure of the entire text. Paying attention to questions, problems, or issues already implies a form of intention: preparing the foundation for the structure as the integral didactic aspect of the text. The ground of this didactic idea is Husserl’s notion of active synthesis, which can be presented using digital technology. For this purpose, the background to this attempt is first presented, followed by its practical implementation and the digital aspect that constitutes its contribution to Digital Humanities.